Behavioral Patterns of Children Involved in Bullying Episodes - Santoyo, Carlos V.; Mendoza, Brenda G. (Frontiers in Psychology, 2018)
This study applied a systematic observation strategy to identify coercive behavioral patterns in school environments. The aim was to describe stability and change in the behavioral patterns of children identified as victims of bullying. To this end, the following specific objectives were defined: 1) to identify episodes of bullying based on the frequency of negative behaviors received and power imbalances between bully and victim; 2) to describe stability and behavioral changes in students based on their social and academic conduct and the aggression they receive from peers and teachers; and 3) to describe the functional mechanisms responsible for the process of social organization (i.e., the Social Effectiveness, Social Responsiveness and Social Reciprocity Indexes). The sample consisted of nine children identified as victims, nine classified as bullies, and nine matched controls, all elementary school students from the study developed at the National Autonomous University of Mexico files. A multidimensional / idiographic / follow-up observational design was used. Observational data describes asymmetry between victims and bullies based on microanalyses of the reciprocity of their behavioral exchanges. In addition, the behavioral patterns of victimized children were identified in relation to their academic activity and social relationships with peers. A model of coercive reciprocity accurately describes the asymmetry found among bullies, victims and controls. A reduction in victimization was found to be related to: 1) responsiveness to the initiation of social interactions by peers and teachers; and 2) the time allocated to academic behavior during the study.